Website Information Application At Islamic junior School Ash-Syarief Using Macromedia Dreamweaver MX 2004 - Dede Nur'aidah (Jurnal Sistem Informasi, 2007)
Internet media today are very degemari by the community, because the Internet is one ofthe containers / facilities highly efficient and effective way to exchange information. Inscientific writing, the author makes the website of Islamic junior high ash-Starief usingMacromedia Dreamweaver MX 2004 which contains all information about Islamic juniorhigh ash-Syarief, among others: History of Islamic junior high ash-Syarief, Vision andMission Junior High School Ash-Syarief Islam, curriculum, facilities, extracurricularactivities, school participation, School Leadership, Location Map, Contact Us, and theguestbook. In addition to the author using SwishMax program, PHP, and MySQL as aprogram supporter.